Fabric Studies on a 1 Meter-Deep Snow Core from Mizuho Plateau, East Antarctica - Masayoshi NAKAWO (National Institute of Polar Research, 1975)
Petrofabric analyses were carried out on a snow core from the surface to a depth of one meter obtained at S100 (69°38.1'S; 42°51'E; 1,630m above sea level) in Mizuho Plateau, East Antarctica. In order that the distribution of c-axes of snow crystals was examined, the concept of the value of X^2 was introduced and "the degree of vertical c-axis concentration" was defined. Although the predominance is in the horizontal direction as regards the degree of c-axis concentration in snow layers near the surface, this predominance periodically alternates between the horizontal and the vertical direction as the depth increases, gradually strengthening a trend for the increasing degree of vertical c-axis concentration. This periodicity shows a fairly good correlation with the positions of autumn layers or depth-hoar layers.